Konstruksi Gender Perempuan Ideal dalam Iklan Sabun Lux Edisi Super Power (dalam Kajian Semiotika Roland Barthes) - Sari, Diana (Center of Gender Studies and Child of State Islamic Institute of Metro, 2020)
Abstract: The gender issues seem to have been completed, but the discussions about gender have never been finished until now. Gender constructs developed in the community have always left traces of women and men on the description of traits, tasks, and gender roles. These portrayals began to be produced by several advertising companies, in which, the most highlighted object in the advertising world is mainly woman. It’s no wonder that women are the favorite target of various parties and professions, bothphotographers and cameramen, advertisers, marketers, and so on. The attraction of women is indeed very unique and specific that can be noticed by men. Not only is the female body posture that brings attraction, namely from hair to toe, women's attractiveness can also be seen from her behaviour. Everything is very interesting,not even for the opposite sex only, but also for other women themselves. One of the ads that constructs about the characteristics of women so prominently is the super power edition of Lux soap ads that shows the criteria of the ideal woman of the moment. Discourse on women's mass media advertising is often positioned not as a subject but instead as an object sign. Regarding to the sign, the author uses semiotic analysis.Keyword: Gender, Ideal woman, and Advertisement. Abstrak: Permasalahan Gender sepertinyatampak sudah selesai, namun pembahasan gender tidak pernah ada habisnya sampai saat ini. Konstruk gender yang berkembang di masyarakat sejak dulu masih menyisakan bekas terhadap perempuan dan laki-laki mengenai penggambaran sifat-sifat, tugas-tugas, dan peran gender. Penggambaran tersebut mulai diproduksi oleh beberapa pihak iklan, yang sering disorot dalam dunia periklanan adalah kaum perempuan. Tidak heran jika perempuan menjadi sasaran favorit berbagai pihak dan profesi, baik fotografer, kameramen, pengiklan, pemasar, dan sebagainya. Daya tarik perempuan tersebut memang sangat khas, unik, dan spesifik yang bisa ditemui oleh laki-laki. Tidak saja postur tubuh perempuan yang mendatangkan daya tarik yaitu dari rambut sampai ujung kaki, daya tarik perempuan juga dapat dilihat dari perliakunya. Semuanya sangat menarik perhatian, bahkan tidak saja lawan jenis, tetapi juga bagi sesama perempuan itu sendiri. Salah satu iklan yang mengkonstruk tentang sifat-sifat perempuan yang ditampilkan cukup menonjol yaitu iklan sabun lux edisi super power yang menunjukkan ciri-ciri perempuan yang menjadi idaman saat ini. Wacana iklan media massa perempuan sering diposisikan bukan sebagai subyek tetapi sebaliknya sebagai obyek tanda (sign object). Berkaitan dengan tanda tersebut penulis menggunakan analisis semiotika.